Enhancement of methane detection using graphene-doped zinc oxide with Blynk internet of things for real-time monitoring - Siti Amaniah Mohd Chachuli; Fatin Liyana Syakinah Mohd Yatim; Nur Hazahsha Shamsudin; Omer Coban (Institute of Advanced Engineering and Science, 2026)
Methane is a potent greenhouse gas, significantly contributing to global warming gases when released into the atmosphere. Methane, a naturally occurring gas, has no harmful impacts on human life at low concentrations. As concentrations rise, symptoms like fatigue, headaches, nausea, irritability, and speech difficulties increase due to asphyxiation. Zinc oxide (ZnO) and graphene-doped ZnO gas sensors were fabricated using a screen-printing technique onto a Kapton film to compare their performance to methane gas at room temperature. A silver paste was used as the interdigitated electrode, deposited on the Kapton film using a screen-printing technique, and fired at 150 °C for 15 minutes. Next, ZnO and graphene-doped ZnO pastes were deposited onto the interdigitated electrode using a screen-printing technique and became the second layer of the gas sensor. The sensing layer was annealed at 200 °C for 60 minutes. All gas sensors responded well to methane gas at room temperature. As a comparison, the graphene-doped ZnO gas sensor responded better to 6,700 ppm of methane gas than the ZnO gas sensor at room temperature. The highest response of graphene-doped ZnO to methane gas was produced by 5 wt. % of graphene doped into ZnO with a response value of 11.5.